2022
DOI: 10.3390/healthcare10122562
|View full text |Cite
|
Sign up to set email alerts
|

Rubella Virus Infections: A Bibliometric Analysis of the Scientific Literature from 2000 to 2021

Abstract: Rubella virus (RuV) generally causes a mild infection, but it can sometimes lead to systemic abnormalities. This study aimed to conduct a bibliometric analysis of over two decades of RuV research. Medical studies published from 2000 to 2021 were analyzed to gain insights into and identify research trends and outputs in RuV. R and VOSviewer were used to conduct a bibliometric investigation to determine the globally indexed RuV research output. The Dimensions database was searched with RuV selected as the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…All the mentioned countries are economically developed. Similar to our findings, previous studies on scientific productivity have shown that economically developed countries are more productive regarding scientific studies (16)(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All the mentioned countries are economically developed. Similar to our findings, previous studies on scientific productivity have shown that economically developed countries are more productive regarding scientific studies (16)(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 92%
“…It causes an increasing number of cases, especially in children and immunosuppressants, owing to respiratory tract infections ( 3 , 4 ). Although bibliometric studies, a popular method today, have been conducted for many popular or traditional infectious etiologic agents and viruses ( 14 , 16 - 19 ), our study is the first to evaluate hMPV in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…En consecuencia, se recurre a comparaciones con áreas de las ciencias de la salud, como punto de referencia. Por ejemplo, la cifra reportada en el presente estudio es inferior a la reportada por Catalá-López et al ( 2023) de un total de 662 publicaciones (97,2%) sobre pautas para la presentación de informes de investigación en salud, igualmente a las presentadas por Barrera-Suarez et al ( 2021) en un análisis bibliométrico sobre revistas de optometría (94%) y publicaciones sobre la variante OMICRON del SARS-CoV-2 (96%) (Ejaz et al, 2022). En relación con el género, se observa una escasa participación de mujeres en las publicaciones académicas (menos del 30%).…”
Section: Discussionunclassified
“…On the contrary, rubella’s effects on neurodevelopment have been widely investigated. Rubivirus is an enveloped single-stranded RNA virus belonging to the Matonaviridae family, and it is known to infect the fetal brain directly, causing neuronal death, gliosis, and a disruption of mitosis ( Brown et al, 2000 ; Ejaz et al, 2022 ). Congenital rubella syndrome includes systemic symptoms, such as cataracts or congenital glaucoma, congenital heart disease, hearing impairment, and pigmentary retinopathy ( Gordon-Lipkin et al, 2021 ).…”
Section: The Impact Of Other Prenatal Respiratory Infection On Neurop...mentioning
confidence: 99%